Hubungan Dukungan Keluarga Terhadap Praktik Pemberian ASI Eksklusif Dan Status Gizi Bayi - Amina Ahmad; Mirna Mirna; Nur Hidayah MS; Kartini Kartini (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2026)
Exclusive breastfeeding is an important factor in improving infant nutritional status and reducing morbidity and mortality rates. One of the determinants of successful exclusive breastfeeding is family support. This study aimed to determine the relationship between family support and the practice of exclusive breastfeeding and infant nutritional status. This research used an analytical design with a cross-sectional approach. The sample consisted of 60 mothers with infants aged 0–6 months. Data were collected using questionnaires and measurements of infant nutritional status based on weight-for-age indicators. Data analysis was performed using the chi-square test. The results showed that the majority of respondents had good family support (66.7%), practiced exclusive breastfeeding (61.7%), and had infants with normal nutritional status (73.3%). There was a significant relationship between family support and exclusive breastfeeding (p = 0.01), as well as between exclusive breastfeeding and infant nutritional status (p = 0.02). In conclusion, family support plays an important role in the success of exclusive breastfeeding and contributes to improving infant nutritional status.